(3GNJjGQ GdQajb dWdGH GdWQjb (B((3aj WHbGJ GdUhajg(B)s - (3CHj GdYHGS CMeO Hf SdGeg Hf QHGM eMeO Hf SdGeg Hf eSde GdebOSj GdeUQj GdhGYX, TgGH GdOjf,J (B769 (3g` s ((3eMeO Hf YHOGddWja GdLhjfi GdCRgQi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOi CfhGQ eYQaJg dbdhH GdYGQajf Ef HYV ENhGf GdhaG SCdfi JCdja eNJUQ CLeY ajg ef CSeGA eTGjN GdSGOg GdUhajI eG JaQb ai cKjQ ef GdeUfaGJ s
(3BNQgG (B:s
(3hde jRd jHci MJi Hd dMjJg hKhHg aQMeg ef cKQI GdHcGA Ke CdJaJ Edi hbGd hGdMeO ddg QH GdYGdejf hcGf GdaQGZ ef cJGHJg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B148 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B13 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B- (3HGdgfO (B(344) s
Keywords: (3GdJGQjNs